Os poderes do juiz no novo Código Civil - Tosta, Jorge (2006)
The New Civil Code has brought great innovations in comparison to the last one in 1916. Taking this into consideration, the aim of this study is to present a reflection on the new role judges play from the New Civil Code in interpreting and applying juridical models in the private law scope as well as a proposal of controlling the juridical aspect of this integrating-interpretation. As the New Civil Code has introduced various new open-like models characterized by vague or undetermined terms and others, which confer the judge the power to act according to his chance of opinion, the New Civil Code drives away the rationalistic justice belief in the law empire. In it, all situations were ruled and solved in a conceptualized way by the statuary law itself. In this perspective, the judge was only the mouth that pronounces the words of law . At the current time, the New Civil Code delegates to the judge a filling gap task of terms in vague juridical concepts consonant with social cultural context as well as from axiological elements or experience rules provided by observation than it usually occurs. It also has delegated to the judge the ability to decide certain struggles or define specific situations in a discretionary way. From a qualitative approach of investigation, this bibliographical study took data derived from observation and law direct participation, from jurisprudence and from doctrine, even in Comparative Law, we tried to identify and classify such open like models in the New Civil Code. Then, in order to prove that, in relation to these models characterized by vague or undetermined terms, the judge does not act in a discretionary way since he accomplishes a repeatedly astringent process than standards, values and general law principles that allow him to get to the only correct solution. In relation to the open-like models characterized for conferring the judge, positively, the power to decide according to the chances of opinion and convenience, even though an astringent process does not take place, the judge is also still tied to standards, values and principles which indicate among the solutions, the best one. After we have determined the criteria and/ or parameters, and also the limits for the juridical concretization of the open-like models, a possibility of controlling the juridical aspect of the integrating-interpretation accomplished by the judge was pointed out indicating the possible occurring defects in this process